Compensatory bladder behaviors (“coping”) in women with overactive bladder - Reynolds, William Stuart; Kaufman, Melissa R.; Bruehl, Stephen; Dmochowski, Roger R.; McKernan, Lindsey C. (Neurourology and urodynamics, 2022)
ABSTRACT Aims There is little information on how often or within what contexts individuals with OAB use compensatory behaviors (“coping”) to manage symptoms. We sought to examine how frequently women with OAB report using coping behaviors and whether these are associated with psychosocial factors. Methods One hundred twenty adult women with OAB completed the OAB questionnaire (OAB‐q), ICIQ‐FLUTS questionnaire, PROMIS Anxiety and Depression, Perceived Stress Scale, patient perception of bladder condition, and demographic and clinical data. Responses from five items from the OAB‐q Quality‐of‐Life scale asking about coping with OAB symptoms (i.e., “compensatory coping behaviors”) were summed to generate a total Coping Score. Linear regression was used to identify associations between individual coping behaviors, total Coping Scores, and exposure variables. Results Most (88%) subjects reported using at least one compensatory coping behavior at least “a little of the time,” with “locating the nearest restroom in a new place” the most frequent. Higher BMI, lower education, using OAB medication, and urgency incontinence as well as urinary symptom severity were all associated with higher coping scores. Beyond the influence of OAB severity, higher anxiety (β = 0.15, 95% CI [0.05–0.26], p = 0.004) and stress (β = 0.16 [0.03–0.25], p = 0.02) were significantly associated with higher total coping scores, although depression was not. Conclusions Compensatory bladder behaviors (coping) were common in women with OAB and were associated with greater urinary symptom severity and higher anxiety and stress. Further study is needed to understand how coping behaviors and psychosocial factors relate, as these may represent important opportunities for interventions.